Strategi Bauran Promosi Film ‘’Cek Toko Sebelah’’ oleh PT Kharisma Starvision Plus - Oktaviana, Nadya; Sudrajat, Ratih Hasanah (Media Nusantara, 2021)
Nowadays, the development of cinema in Indonesia increasing every year. This makes the existing production houses compete against each other. PT Kharisma Starvision Plus is one of the production houses in Indonesia that has existed since 1995 and founded by Chand Parwez ServiaServia. One of the Starvision films that became box office in 2016 is the ‘’Cek Toko Sebelah’’ Film. This research discusses how promotion planning strategy, how promotion mix strategy and how to evaluate the result of execution of promotion mix strategy of ‘’Cek Toko Sebelah’’ Film by PT Kharisma Starvision Plus. The method used in this research is qualitative descriptive with using constructivism paradigm. Data collection techniques were interviewed with two key informants from PT Kharisma Starvision Plus, one marketing expert, two supporting informants, and qualitative documents. The results of this study indicate that the Check Store Movement by doing promotion planning, using 5 promotion mix that is advertising through print media, electronic media, outdoor media, and digital media; sales promotion through free gifts, a quiz with prizes, contests, and merchandise: public relations through the press conference, roadhshow, campus visit, media cooperation, active on social media and website; direct sales and direct marketing through the LINE Messenger application.